Latitude Effect on Carbon, Nitrogen and Oxygen Stable Isotope Ratios - Katsura, Hidemitsu (Asian Journal of Chemistry, 2012)
Cosmic rays in the upper troposphere (30000 feet to 50000 feet; 9000 meters to 15000 meters) initiate the nuclear chemical reaction: 1n + 14N => 14C + 1H. Previous research has shown a strong effect of latitude on the abundance of neutrons from cosmic rays. However, to date, there has been little exploration of the relationship between the latitude effect for cosmic-ray neutrons and latitudinal variations of stable isotope ratios in aerosols and foliage. In this study, aerosol samples (PM 4.5) and foliage samples were collected in Singapore in November 2009, February 2010 and July 2010 and in Fairbanks, Alaska, U.S.A. in January 2010, April 2010 and September 2010. Ion chromatography, gas chromatography-mass spectrometry, and element mass spectrometry were used to measure anion concentrations and nitrogen and oxygen stable isotope ratios in nitrogen oxide ions of the aerosol samples, as well as to measure carbon and nitrogen stable isotope ratios in the foliage samples. The average value of d15/14N in foliage in Fairbanks was -1.84 [per mil], whereas the average value in Singapore was -1.3 [per mil]. These results show a clear latitude effect on d15/14N in foliage. Furthermore, the average value of d15/14N in the nitric-oxide substances in the aerosol samples in Fairbanks was -2.70 [per mil], whereas the average value in Singapore was +7.61 [per mil], demonstrating that d15/14N in nitric-oxide substances from aerosol samples also experiences a latitude effect. However, no clear latitudinal pattern was observed for d13/12C in foliage or for d18/16O in nitric-oxide substances from aerosols. In both Singapore and Fairbanks, it was observed that values of d15/14N in nitric-oxide substances from aerosols were correlated with declination. The value of d15/14N in nitric-oxide substances from aerosols in Fairbanks increased with increasing declination due to more active conversions from 14N to 14C by neutron bombardment.